COMPARISON OF ZOOPLANKTON ABUNDANCE UNDER SEA ICE BETWEEN NIPR NET AND NORPAC NET SAMPLINGS, IN LAGOON SAROMA KO, HOKKAIDO (Ninth Symposium on Polar Biology) - ニシヤマ, ツネオ; タニムラ, アツシ; ワタナベ, ケンタロウ; フクチ, ミツオ; アオタ, マサアキ; NISHIYAMA, Tsuneo; TANIMURA, Atsushi; WATANABE, Kentaro; FUKUCHI, Mitsuo; AOTA, Masaaki (National Institute of Polar Research, 1987)
P(論文) Zooplankton under sea ice were collected vertically and horizontally at two stations (7-11 m depth) in lagoon Saroma Ko, Hokkaido, on February 21-24,1986, and their abundance was compared by haul, mesh size, depth, sampling duration, and sampling station. Vertical hauls from the bottom to the surface were made with a standard Norpac net and its modified net, and horizontal samplings with a NIPR net (under-ice plankton sampler) from 0.3,2 and 5 m, and bottom layers. Three mesh sizes, 100, 330 and 505 μ, were used for each net. Copepods (mostly Pseudocalanus sp.) and chaetognath (Sagitta elegans) predominated the biomass in weight and number with a few amphipods. In vertical hauls with 100 μ-mesh Norpac net, the copepod abundance was similar between the two stations, while the chaetognath abundance was significantly greater at Stn. 11 than at Stn. 3. In horizontal samplings with the 100 μ-niesh NIPR net, copepods were very abundant in the 0.3 and 2 m layers, but were fewer in the 5 m and bottom layers. Chaetognath revealed a distinct vertical stratification with a highest abundance in the 2 m layer and scarcity in the 0.3 m and bottom layers. Compared with a 5-min filtration, the 10- and 15-min filtration in the 330 μ- and 505 μ-mesh NIPR nets showed a decrease of the zooplankton catches per unit time. The modified Norpac net collected significantly abundant chaetognath than the standard Norpac net, but not for copepods. departmental bulletin paper